Charge localization control of electron–hole recombination in multilayer two-dimensional Dion–Jacobson hybrid perovskites. Issue 18 (28th April 2020) - Shi, Ran; Zhang, Zhaosheng; Fang, Wei-Hai; Long, Run
Abstract : Significant charge delocalization in the Dion–Jacobson (4AMP)(MA)Pb2 I7 perovskite enhances non-adiabatic coupling and accelerates non-radiative electron–hole recombination. Abstract : Two-dimensional (2D) Dion–Jacobson (DJ) organic–inorganic hybrid halide perovskites hold great potential for optoelectronics and solar cells. Interestingly, experimental excited-state lifetime is longer in (3AMP)(MA) n −1 Pb n I3 n +1 than (4AMP)(MA) n −1 Pb n I3 n +1 (3AMP = 3-(aminomethyl)piperidinium, 4AMP = 4-(aminomethyl)piperidinium, MA = CH3 NH3 + ) regardless of the value of n despite 3AMP having a smaller bandgap. Using ab initio nonadiabatic (NA) molecular dynamics combined with time-domain density functional theory, we focus on the n = 2 perovskite and demonstrate that stronger hydrogen bonding interaction and larger octahedral tilting cause significant delocalization of the hole wave function in (4AMP)(MA)Pb2 I7 and accelerates the electron–hole recombination by a factor of 5 compared to (3AMP)(MA)Pb2 I7 due to an increased NA coupling. The inorganic component stretching mode and coupled inorganic and organic collective motions accelerate decoherence to sub-4 fs in the two materials. The simulations rationalize the experimentally observed puzzle of excited-state lifetime in the 2D DJ perovskite and suggest a rational way to optimize the performance of perovskite devices.